Insect Science Diversity, Conservation and Nutrition - Manjur Shah, Mohammad; Sharif, Umar (IntechOpen, 2018)
The book discusses the recent advances in basic and applied approaches including research on the genetics of insects, its application in resolving the consequences of world population growth, its impact on agriculture, and control strategies and their implications on the fast-depleting insect resources. The application of insects as a probable nutrient substitute along with the role of sex hormones among insects has been thoroughly discussed. The entire book basically contains five chapters spread over two sections: Section I mainly focuses on diversity, conservation and nutrition, while Section II is concerned with economic importance and up-to-date information on the role of peptides. The book is well illustrated with diagrams, graphical representations and flow charts for easy understanding the important information discussed in the book.